Conditioning factors for the scientific productivity of undergraduate students of health sciences at a private Peruvian University: A cross-sectional analytical study [version 3; peer review: 2 approved] - Oriana Rivera-Lozada; Isabel Cristina Rivera-Lozada; César Antonio Bonilla-Asalde (F1000Research)
Background The objective of this study was to determine the conditioning factors for scientific research productivity in university students of health sciences. Scientific productivity, in addition to making visible the generation of new knowledge, contributes to the well-being of the population and provides feedback to the scientific community in terms of methodologies, perspectives and results that help to break down barriers that delimit productivity in scientific research. Methods A cross-sectional analytical observational study was conducted. The study population was 4104 students enrolled during the 2021-I semester in the Faculty of Health Sciences of a private Peruvian university. A sample size of 400 students was determined and a stratified probability sampling was used. The variables were measured through surveys. The dependent variable was scientific research productivity, and the independent variables were institutional culture, knowledge management and technological capital. Summary measures are reported according to the type of variable. The chi-square test with a significance level of p<0.05 was applied to assess the association between the variables of interest. A multiple logistic regression analysis was performed using the Stepwise method. Prevalence ratios (PR) with their respective 95% confidence intervals (95%CI) were calculated. Results From the total of 400 students, 74.5% were male, 57.25% were aged between 18 and 27 years, 17% belonged to the school of human medicine and 72% were in their sixth year of studies. Scientific research productivity was associated with management commitment (PR=1.493; 95%CI: 1.077–2.068, p=0.015), sense of personal growth (PR=1.632; 95%CI: 1.041–2.558; p=0.024), recognition by the university (PR=1.385; 95%CI: 1.012–1.896; p=0.043), strategic alliances (PR=1.422; 95%CI: 1.032–1.959; p=0. 03), having research proposals (PR=1.522; 95%CI: 1.114–2.08; p=0.009), dissemination of results obtained (PR=1.542; 95%CI: 1.12–2.122; p=0.01), availability of human resources (PR=1.591; 95%CI: 1.165–2.173; p=0.004), access to equipment and software (PR=1.482; 95%CI: 1.061–2.069; p=0.018) and to laboratories (PR=1.438; 95%CI: 1.047–1.974; p=0.024). Conclusion It is concluded that the research productivity of undergraduate students of health sciences is low. It is imperative to strengthen the university research culture that empowers students as agents of change and strengthens faculty participation in scientific networks and communities.